2014
DOI: 10.1136/gutjnl-2014-307387
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression alterations in ulcerative colitis patients after restorative proctocolectomy extend to the small bowel proximal to the pouch

Abstract: Significant gene expression alterations exist in an apparently unaffected proximal SB. Alterations in the pouch and the proximal SB were comparable, suggesting that inflammation may not be limited to the pouch, but that it extends to the proximal SB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…This finding suggested that mucosal inflammation may not be limited to endoscopic lesions in the gut, and that molecular abnormalities may better diagnose an impairment of intestinal homeostasis and subclinical intestinal inflammation. Consistent with these results, a previous study demonstrated that there were marked overlaps in the gene expression alterations between the small bowel proximal to the pouch and the pouch itself in patients with UC following restorative proctocolectomy (23).…”
Section: Discussionsupporting
confidence: 81%
“…This finding suggested that mucosal inflammation may not be limited to endoscopic lesions in the gut, and that molecular abnormalities may better diagnose an impairment of intestinal homeostasis and subclinical intestinal inflammation. Consistent with these results, a previous study demonstrated that there were marked overlaps in the gene expression alterations between the small bowel proximal to the pouch and the pouch itself in patients with UC following restorative proctocolectomy (23).…”
Section: Discussionsupporting
confidence: 81%
“…A critical function of DUOX2 in the epithelial defense response against the abundant intestinal microbiota would be consistent with the robust upregulation of DUOX2 in conditions frequently associated with dysbiosis, even in the absence of manifest inflammation. For instance, DUOX2 is markedly upregulated in the intestine of patients with irritable bowel syndrome 7 , in the normal appearing proximal small intestine after ileal pouch-anal anastomosis 8 , and in noninflamed ilea of patients with colon-only Crohn’s disease (cCD) 9 . However, whether DUOX2 induction is a consequence of microbial dysbiosis and plays a role in maintaining immune homeostasis is currently unclear.…”
mentioning
confidence: 99%
“…The finding that disease severity prior to surgery is associated with pouch outcome may reflect the fact that pathological changes exist in IBD patients (both CD and UC) even in areas that are grossly normal, and that such changes may be associated with disease severity and not exist among normal controls …”
Section: Discussionmentioning
confidence: 99%